Effect of Treatment with Salsalate, Menhaden Oil, Combination of Salsalate and Menhaden Oil, or Resolvin D1 of C57Bl/6J Type 1 Diabetic Mouse on Neuropathic Endpoints. (28th September 2016) - Yorek, Matthew S.; Coppey, Lawrence J.; Shevalye, Hanna; Obrosov, Alexander; Kardon, Randy H.; Yorek, Mark A.
Abstract : Aims . In this study a streptozotocin induced type 1 diabetes mouse model was used to assess the effectiveness of salsalate, menhaden oil, the combination of salsalate and menhaden oil, or resolvin D1 on neuropathic endpoints. Materials and Methods . Changes in body weight, blood glucose, serum markers for triglycerides, free fatty acids, cholesterol, and resolvin D1, motor and sensory nerve conduction velocities and thermal sensitivity were assessed, as well as performing in vivo confocal microscopy of subepithelial corneal nerves and immunohistochemistry of nerves in the cornea and foot pad. Results . Diabetic animals failed to gain weight and had elevated blood glucose levels. Diabetic mice had slowed nerve conduction velocity, reduced innervation of the foot pad and cornea subepithelial and epithelial layers, and reduced thermal sensitivity. Monotherapy treatment with salsalate, menhaden oil, and resolvin D1 reduced the pathological signs of diabetic neuropathy. The combination of salsalate and menhaden oil also reduced signs of pathology and generated elevated plasma levels of resolvin D1 compared to other groups. Conclusions . Additional studies are needed to determine whether the combination of salsalate and menhaden oil may be more efficacious than monotherapy alone for the treatment of diabetic peripheral neuropathy.